Strengthening the Governance of Cash Waqf-Linked Sukuk: Legal Recognition, Regulatory Challenges, and Harmonization (Jurnal Hukum Islam, 2026)
Cash Waqf-Linked Sukuk (CWLS) is a strategic instrument for developing productive waqf and national social financing. However, its regulation is still administrative and relies on delegated regulations, thus not fully guaranteeing transparency, efficiency, and accountability. Therefore, this research aimed to analyze the regulations governing CWLS in Indonesia and identify structural gaps in the normative hierarchy that trigger regulatory fragmentation, information asymmetry, and accountability deficits in multi-actor governance. Adopting normative juridical methods and philosophical, statutory, and conceptual approaches, this study finds a crucial misalignment between current waqf law and fundamental sharia values, particularly maṣlaḥah (public benefit) and justice. This study offers a conceptual reconstruction of Cash Waqf Linked Sukuk governance through the integration of maqaṣid al-syari‘ah and Critical Legal Studies.The proposed reforms emphasize a strong harmonization agenda by elevating core protections such as corpus preservation, standardized rollover protocols, and digital-based information disclosure to a higher legal regulatory mandate. In conclusion, this research shows that a reorientation of the legal framework bridging the gap between legal certainty and substantive justice is an absolute prerequisite for ensuring public trust and the sustainable socio-economic impact of waqf-based state finance, both nationally and globally.
Keywords: Cash Waqf Linked Sukuk; Maqaṣid al-syari‘ah; Regulatory; Waqf governance